Antibodies Elicited by the Shigella sonnei GMMA Vaccine in Adults Trigger Complement-Mediated Serum Bactericidal Activity: Results From a Phase 1 Dose Escalation Trial Followed by a Booster Extension - Micoli, Francesca; Rossi, Omar; Conti, Valentino; Launay, Odile; Sciré, Antonella Silvia; Aruta, Maria Grazia; Nakakana, Usman Nasir; Marchetti, Elisa; Rappuoli, Rino; Saul, Allan; Martin, Laura B.; Necchi, Francesca; et al. (Frontiers in Immunology, 2021)
Shigella is the second most deadly diarrheal disease among children under five years of age, after rotavirus, with high morbidity and mortality in developing countries. Currently, no vaccine is widely available, and the increasing levels of multidrug resistance make Shigella a high priority for vaccine development. The single-component candidate vaccine against Shigella sonnei (1790GAHB), developed using the GMMA technology, contains the O antigen (OAg) portion of lipopolysaccharide (LPS) as active moiety. The vaccine was well tolerated and immunogenic in early-phase clinical trials. In a phase 1 placebo-controlled dose escalation trial in France (NCT02017899), three doses of five different vaccine formulations (0.06/1, 0.3/5, 1.5/25, 3/50, 6/100 µg of OAg/protein) were administered to healthy adults. In the phase 1 extension trial (NCT03089879), conducted 2–3 years following the parent study, primed individuals who had undetectable antibody levels before the primary series received a 1790GAHB booster dose (1.5/25 µg OAg/protein). Controls were unprimed participants immunized with one 1790GAHB dose. The current analysis assessed the functionality of sera collected from both studies using a high-throughput luminescence-based serum bactericidal activity (SBA) assay optimized for testing human sera. Antibodies with complement-mediated bactericidal activity were detected in vaccinees but not in placebo recipients. SBA titers increased with OAg dose, with a persistent response up to six months after the primary vaccination with at least 1.5/25 µg of OAg/protein. The booster dose induced a strong increase of SBA titers in most primed participants. Correlation between SBA titers and anti-S. sonnei LPS serum immunoglobulin G levels was observed. Results suggest that GMMA is a promising OAg delivery system for the generation of functional antibody responses and persistent immunological memory.